Nature and type of patient-reported safety incidents in primary care: cross-sectional survey of patients from Australia and England. Issue 4 (29th April 2021) - Hernan, Andrea L; Giles, Sally J; Carson-Stevens, Andrew; Morgan, Mark; Lewis, Penny; Hind, James; Versace, Vincent
Abstract : Background: Patient engagement in safety has shown positive effects in preventing or reducing adverse events and potential safety risks. Capturing and utilising patient-reported safety incident data can be used for service learning and improvement. Objective: The aim of this study was to characterise the nature of patient-reported safety incidents in primary care. Design: Secondary analysis of two cross sectional studies. Participants: Adult patients from Australian and English primary care settings. Measures: Patients' self-reported experiences of safety incidents were captured using the validated Primary Care Patient Measure of Safety questionnaire. Qualitative responses to survey items were analysed and categorised using the Primary Care Patient Safety Classification System. The frequency and type of safety incidents, contributory factors, and patient and system level outcomes are presented. Results: A total of 1329 patients (n=490, England; n=839, Australia) completed the questionnaire. Overall, 5.3% (n=69) of patients reported a safety incident over the preceding 12 months. The most common incident types were administration incidents (n=27, 31%) (mainly delays in accessing a physician) and incidents involving diagnosis and assessment (n=16, 18.4%). Organisation of care accounted for 27.6% (n=29) of the contributory factors identified in the safety incidents. Staff factors (n=13, 12.4%) was the second most commonly reported contributory factor. Where an outcome could be determined, patient inconvenience (n=24, 28.6%) and clinical harm (n=21, 25%) (psychological distress and unpleasant experience) were the most frequent. Conclusions: The nature and outcomes of patient-reported incidents differ markedly from those identified in studies of staff-reported incidents. The findings from this study emphasise the importance of capturing patient-reported safety incidents in the primary care setting. The patient perspective can complement existing sources of safety intelligence with the potential for service improvement.